2014
DOI: 10.15680/ijirset.2014.0308016
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Extraction and Characterization of the Leaves of Andrographis Paniculata for Its Anti-Bacterial, Anti-Oxidant, Anti-Pyretic and Anti-Diabetic Activity

Abstract: Andrographis paniculata Nees.,a member of the family Acanthaceae is a plant commonly used by the local people, for the treatment of common cold, liver diseases, snake bite and some skin infection. The aerial part of the plant was screened for their phytochemical properties and antimicrobial activity. Antimicrobial activity of leaf extract of Andrographis paniculata, was studied using different solvent like chloroform, methanol, petroleum ether and water against bacterial strains like Bacillus subtilis, Escheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…The aloe-gel extract at the concentration of 100μg/ml showed 25 mm diameter zone of inhibition against E. coli. This was followed by 20, 18 and 15.5 mm zone of inhibition against B. subtilis, B. cereus and S. aureu 4 .…”
Section: Xrd Analysis Ofmentioning
confidence: 88%
“…The aloe-gel extract at the concentration of 100μg/ml showed 25 mm diameter zone of inhibition against E. coli. This was followed by 20, 18 and 15.5 mm zone of inhibition against B. subtilis, B. cereus and S. aureu 4 .…”
Section: Xrd Analysis Ofmentioning
confidence: 88%
“…Browning decreases the explant survival and leads to failures in shoot regeneration (Roy and Sarkar, 1991). A suitable carbon source and antioxidants (ascorbic and citric acids) need to be added to avoid excessive phenolic secretion in the culture medium (Das and Srivastav, 2015). To eliminate blacking and browning, PVP can be used (Roy and Sarkar, 1991; Liao et al, 2004; Rathore et al, 2011b).…”
Section: Propagation Techniquesmentioning
confidence: 99%
“…Growing in relatively high moistures and shady places, the extent of its height can reach up to 110 cm. With the characteristics of dark green slender stem and hairless lanceshaped leaves, this plant also bears fruits in the shape of a small capsule [17]. Several studies showed the anti-oxidant effect of Kalmegh aqueous extract originates from its capability to activate the antioxidant enzymes which induce the oxidants reaction [18].…”
Section: Introductionmentioning
confidence: 99%